Senjata Api sebagai Mas Kawin Pada Masyarakat Adat di Pegunungan Arfak Papua Barat - Caprina, Decyana; Saleng, Abrar; Azisa, Nur (Al-Mizan (e-Journal), 2024)
This study aims to analyze the validity of firearms as dowry and the legal consequences arising from the existence of Papuan customary law in the Arfak Mountains of West Papua. This research is a normative-empirical research with a statutory approach and a legal sociology approach. The types and sources of law used in this research are primary data sourced from observation, interviews, and documentation, as well as secondary data derived from literature. Furthermore, the collected data is analyzed with qualitative description.  The results showed that: (1) the validity or legality of firearms as a dowry does not apply to the marriage of the mountain people of the Arfak tribe. This is because firearms can only be owned by law enforcement officers and security forces who have permission to use firearms; (2) the legal consequences of the enactment of Arfak tribal customs regarding the provision of firearms as dowry are considered valid because firearms are only a symbol in the customs of indigenous tribes and are considered to have historical values that have been passed down from generation to generation, and are not an aspect that cancels a marriage.